The concept of Waqf sukuk and its ruling in Islamic law - Negasi, Mohamed Ibrahim; Laeba, Muhammad; Abubakar, Yusuf Sani (Scholars Academic and Scientific Publisher s (SAS Publishers), 2018)
This is a study on Waqf Sukuk, which is a fairly new concept of waqf. The paper begins by first defining Sukuk and Waqf . The discussion then continues with an analysis of the meaning of Waqf Sukuk and how it may be applied in modern times. The study also looks into the mechanism, steps and rules for the issuance of a valid Waqf Sukuk. The research also studies the rules o f Waqf Sukuk in the secondary market by explaining the rulings on temporary Waqf and discusses the opinions of scholars on the issue. In the analysis of primary sources relating to this issue, the researchers rely on inductive, descriptive and analytical m ethods of document analysis. The study concludes with a view that prefers cash Waqf and temporary Waqf and thus allows the issuance and trading of Waqf Sukuk.